Effects of substrate composition on the activity of amylase produced by Aspergillus niger - Olympia, Minerva S.; Alabastro, Estrella F. (1982)
Solid state cultivation of Aspergillus niger on two different types of substrates namely, corn bran and rice bran, was done. Culture filtrates from corn bran produced a consistently higher activities of total amylases, total glucoamylases, and glucoamylase I than that from rice bran. The amylase produced from corm bran cultures was also found to be active in raw starch digestion. In view of the above results, corn bran was used as the substrate for the enzyme production in the secons phase of the study. In the second phase, the effect of the addition of the supplementary carbon and nitrogen sources into medium on the enzyme activities was studied. Results showed that enzyme activities can be enhanced by carbon and nitrogen supplementation. Three different types of starch and four types of ammonium compounds were tested as supplementary sources of carbon and nitrogen, respectively. The effect of the type of starch as carbon source on the enzyme activity was not statistically significant except for total glucoamylase activity. Total amylase, total glucoamylase, glucoamylase I activities and raw starch hydrolysis were found to be higher in the medium supplemented with urea or ammonium citrate. Poor growth and lower enzyme activities were observed when ammonium acetate was added as supplementary nitrogen source. Varying amount of urea added to corm bran supplemented with 10% potato starch did not show any definite trend in its effect on the enzyme activities. The effects of moisture level of the medium on activity of the enzyme produced was investigated. Maximum enzyme activity was observed at 55% moisture. Beyond this moisture level, total amylase, total glucoamylase, glucoamylase I activities and raw starch digestion decreased. Correlation studies showed significant relationship between raw starch digestion and all the enzyme activities, with total glycoamylase having the highest correlation factor.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Amylases; Amylolysis; Aspergillus niger -- Philippines; Enzymes -- Cultures and culture media